The Effect of Land Area and Labor on Income of Onion Farmers in Naru Barat Village, Sape District, Bima Regency, Nusa Tenggara Barat Province - Mulhaerati; Arniati Arniati; A. Nur Fitrianti A. Nur Fitrianti (Pustaka Digital Indonesia, 2021)
This study aims to determine the effect of land area and labor on the income of onion farmers in the village of West Naru, Sape District, Bima Regency, West Nusa Tenggara Province. The research method used in this research is quantitative research. Sources of data come from observations, interviews and questionnaires. The total population in this study was 220 people, with the sampling using the Slovin formula to 69 respondents. With the technique of data processing using multiple linear regression with the help of SPSS 25 software for windows . The results of the study show that land area has a positive and significant effect on the income of shallot farmers in West Naru Village, Sape District, Bima Regency, West Nusa Tenggara Province. And the workforce has a positive and significant effect on the income of shallot farmers in West Naru Village, Sape District, Bima Regency, West Nusa Tenggara Province